Oral Clostridium butyricum on mice endometritis through uterine microbiome and metabolic alternations - Hagihara, Mao; Ariyoshi, Tadashi; Eguchi, Shuhei; Oka, Kentaro; Takahashi, Motomichi; Kato, Hideo; Shibata, Yuichi; Umemura, Takumi; Mori, Takeshi; Miyazaki, Narimi; Hirai, Jun; Asai, Nobuhiro; et al. (Frontiers in Microbiology, 2024)
Endometritis occurs frequently in humans and animals, which can negatively affect fertility and cause preterm parturition syndrome. Orally administered Clostridium butyricum, a butyrate-producing gram-positive anaerobe, exhibits anti-inflammatory effects. However, the precise mechanism by which Clostridium butyricum attenuates endometritis remains unclear. This in vivo study evaluated the anti-inflammatory effects of orally administered Clostridium butyricum on uterine tissues. In addition, we conducted uterine microbiome and lipid metabolome analyses to determine the underlying mechanisms. Female Balb/c mice were divided into the following four groups (n = 5-20): 1) mock group, 2) only operation group (mice only underwent operation to exposed uterine horns from the side), 3) control group (mice underwent the same operation with the operation group + perfusion of lipopolysaccharide solution from uterine horns), and 4) Clostridium butyricum administration group (mice underwent the same operation with the control group + oral Clostridium butyricum administration from days 0 to 9. Clostridium butyricum was administered via oral gavage. On day 10, we investigated protein expression, uterine microbiome, and lipid metabolism in uterine tissues. Consequently, orally administered Clostridium butyricum altered the uterine microbiome and induced proliferation of Lactobacillus and Limosilactobacillus species. The effects can contribute to show the anti-inflammatory effect through the interferon-β upregulation in uterine tissues. Additionally, oral Clostridium butyricum administration resulted in the upregulations of some lipid metabolites, such as ω-3 polyunsaturated fatty acid resolvin D5, in uterine tissues, and resolvin D5 showed antiinflammatory effects. However, the orally administered Clostridium butyricum induced antiinflammatory effect was attenuated with the deletion of G protein-coupled receptor 120 and 15-lipooxgenase inhibition. In conclusion, Clostridium butyricum in the gut has antiinflammatory effects on uterine tissues through alterations in the uterine microbiome and lipid metabolism. This study revealed a gut-uterus axis mechanism and provided insights into the treatment and prophylaxis of endometritis.